The Teacher’s Strategies in Teaching Vocabulary to 8th Grade Students at MTS Raudlatutta’allum - Dede Meti Agustin Suryani; Elih Haedaroh Muharomah; Khoerunisa (Journal of Applied Linguistics (ALTICS), 2024)
This research explores the effectiveness of incorporating digital tools and resources in vocabulary instruction. The study focuses on the importance of vocabulary acquisition in language proficiency and effective communication skills. The research findings suggest that while the memorization technique is effective in improving vocabulary, it can be time-consuming. Therefore, the study emphasizes the need for contextual learning, word families and associations, active learning strategies, and specific vocabulary strategies. The research provides educators with effective strategies for teaching vocabulary, informs curriculum design, supports differentiated instruction, encourages active learning, and suggests integrating technology in vocabulary instruction. The study utilizes a descriptive qualitative research method, employing interviews as the data collection instrument. The research highlights the perspectives of teachers on strategies to improve students’ vocabulary, with the memorization technique being recognized as beneficial but challenging to implement within the curriculum. The conclusion of the research underscores the significance of vocabulary acquisition and offers valuable insights for educators to enhance vocabulary instruction and support students’ language development. Keywords: Vocabulary instruction, vocabulary acquisition, language profiency, effective communication, active learning, contextual learning, technology integration.